2016
DOI: 10.3109/0886022x.2016.1148936
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus restores podocyte injury and stabilizes the expression of Cabin1 in 5/6 nephrectomized rats

Abstract: Podocyte injury is a vital factor, which induces massive proteinuria. Studies have shown that tacrolimus (TAC) protected podocyte via stabilizing cytoskeleton. Our latest study indicates that calcineurin binding protein 1 (Cabin1) undergoes nuclear translocation during podocytes injury. Whether TAC targets on Cabin1 during podocyte injury is still not clear. This study establishes non-immunological proteinuric model. To observe the effect of the treatment of TAC on Cabin1 expression in 5/6 nephrectomized rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…As IgAN is an immune-complex-mediated glomerulonephritis, immunosuppressants are commonly used for the treatment of the disease. TAC treatment can significantly reduce the dysregulation of Scr, BUN, ALB, and UAE levels [13,14]; studies also found that both TAC and vitamin D have good effect with regards to kidney injury recovery [15,16]. In our study, TAC+VD therapy demonstrated higher potency in normalizing these levels.…”
Section: Discussionsupporting
confidence: 60%
“…As IgAN is an immune-complex-mediated glomerulonephritis, immunosuppressants are commonly used for the treatment of the disease. TAC treatment can significantly reduce the dysregulation of Scr, BUN, ALB, and UAE levels [13,14]; studies also found that both TAC and vitamin D have good effect with regards to kidney injury recovery [15,16]. In our study, TAC+VD therapy demonstrated higher potency in normalizing these levels.…”
Section: Discussionsupporting
confidence: 60%
“…Along with the results of these studies, several studies have investigated the mechanisms of tacrolimus in reducing proteinuria. Tacrolimus was considered to have multifocal mechanisms for reducing proteinuria, such as immunosuppressive mechanisms by suppression of the nuclear factor of activated T cell activity in podocytes [ 17 , 18 ], intraglomerular hemodynamic changes [ 19 21 ], inhibition of the vascular permeability factor [ 22 ], and a direct effect on podocytes [ 8 10 , 23 , 24 ]. Among these mechanisms, we suggested that the early anti-proteinuria effect of tacrolimus was due to reversible hemodynamic changes rather than to other structural changes.…”
Section: Discussionmentioning
confidence: 99%
“…The first aspect is tacrolimus dosage. Several studies evaluating the direct effects of tacrolimus on podocytes have shown that structural changes occur in podocytes when tacrolimus is administered, hence suggesting long duration effects of tacrolimus [ 8 , 23 , 24 ]. In these aforementioned studies, a tacrolimus dose of approximately 0.2–1 mg/kg/day was given; however, these particular studies were performed on animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanically, one possible reason is the depletion of B-and T-lymphocytes or the inhibition of podocyte injury induced by macrolide immunosuppressants or alkylating agents. This was demonstrated in a previous study [1,27,28]. The activation of B-or T-lymphocytes triggers antibody-independent autoimmune damage, which is considered to be the most common cause of nephrotic syndrome [29].…”
Section: Discussionmentioning
confidence: 88%